Exploring older adult narratives of living with a depressed parent - Dzenga, Rachel (University of the Witwatersrand, Johannesburg, 2024)
Research on children of parents living with a mental illness is prevalent in developed countries and has shown that parental depression is linked to a higher risk of adverse outcomes for children. However, less research exists that focuses on older adult narratives, specifically regarding the lived experiences of growing up with a depressed parent. Therefore, this study provided a deeper exploration of older adults reflecting on their childhoods and highlighted the role that narrative hindsight has on the relationships between depressed parents and children. Exploring the narratives of people who grew up with a parent with a depressive disorder was the core interest of this study. Convenience and snowball sampling was used, and seven participants over the age of 60 years in South Africa were interviewed. Narrative theory was used as both a conceptual framework and a methodology, and narrative analysis was used to analyse data from the semi-structured interviews. The findings of the study suggest that the lived experiences of growing up with a depressed parent alter family dynamics and roles in the home, creating parentification in childhood, feelings of unpredictability, chaos, and uncertainty in the home environment. The role of narrative hindsight illuminated ambivalent feelings towards their depressed parents and revealed a significant influence on their own parenting decisions as adults, such as choosing not to have children. Beyond the immediate home environment, social factors such as stigma, institutionalisation and additional support arose as significant factors in the accounts of participants. The study explored the depth of the human experience in the participants’ ambivalence, meaning making, and social context growing up with a depressed parent. Interviewing older adults highlighted the significance of narrative hindsight and its role in understanding how temporality and nostalgia can illuminate the narrative arc between parent and child. Overall, the study illustrated the need for further research in South Africa on older adult narratives that could possibly enrich the knowledge of health practitioners, educators and researchers about the lived experiences of growing up with a depressed parent, assisting with family-based interventions based on a deeper understanding of the effects of parental mental illness over decades.
A research report Submitted in fulfillment of the requirements for a Master of Arts in Community-based Counselling Psychology by coursework and research report, In the Faculty of Humanities , School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; narrative; depression; depressed parents; hindsight; older adults; adverse childhood experiences; SDG-3: Good health and well-being